(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
At present, soil contamination with geohelminths (soil-transmitted helminths) in children’s playgrounds, preschool educational institutions, and kindergartens represents a serious public health concern. Studies conducted worldwide indicate that more than 30–60% of soil samples from children’s playgrounds are contaminated with helminth eggs (for example, 63.5% of playgrounds in the city of Hannover were found to be contaminated). Helminth eggs are able to retain their infective potential for long periods and are transmitted through direct contact with children, leading to intestinal parasitoses and other health problems.